2011
DOI: 10.1186/ar3483
|View full text |Cite
|
Sign up to set email alerts
|

Bone destruction by receptor activator of nuclear factor κB ligand-expressing T cells in chronic gouty arthritis

Abstract: IntroductionThe purpose of this study was to analyze the cellular expressions of pro-resorptive cytokines in gouty tophus tissues, to determine the capacity of monosodium urate monohydrate (MSU) crystals to induce these cytokines, and to understand the mechanisms of bone destruction in chronic gout.MethodsFourteen fixed, paraffin-embedded, uninfected tophus samples were analyzed immunohistochemically. Peripheral blood mononuclear cells (PBMCs) were cultured in vitro with MSU crystals, and gene expression was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 49 publications
2
66
0
2
Order By: Relevance
“…Patients with tophi have enhanced osteoclast formation, and numerous osteoclasts are present adjacent to eroded bone in tophaceous joints [3,55,56]. Osteoblasts may also have a role in bone loss in gout.…”
Section: Cellular Mechanisms Of Joint Damage In Goutmentioning
confidence: 97%
See 3 more Smart Citations
“…Patients with tophi have enhanced osteoclast formation, and numerous osteoclasts are present adjacent to eroded bone in tophaceous joints [3,55,56]. Osteoblasts may also have a role in bone loss in gout.…”
Section: Cellular Mechanisms Of Joint Damage In Goutmentioning
confidence: 97%
“…Factors produced within the tophus are also likely to tip the balance within bone to a proresorptive state. A recent study reported increased expression of receptor activator of nuclear factor-κB ligand (RANKL) in tophus samples from patients with gout, whereas osteoprotegerin expression was largely absent [3]. IL-1β and TNF-α expression within the tophus may also enhance bone resorption [2,3].…”
Section: Cellular Mechanisms Of Joint Damage In Goutmentioning
confidence: 97%
See 2 more Smart Citations
“…Patients with erosive tophaceous gout have fewer osteoblasts present on bone directly adjacent to tophus than bone unaffected by tophus [49], and have osteoclasts within tophi and at the interface between soft tissue and bone [50]. In addition, recent studies demonstrated that tophus tissue was also infiltrated with www.futuremedicine.com inflammatory T cells, which express receptor activators of the NF-kB ligand, the master regulator of osteoclastogenesis, implicating their role in bone destruction [51]. Moreover, tophus-associated monocytes produce the proresorptive cytokines IL-1b, IL-6 and TNF-a, which could further promote osteoclast differentiation [51].…”
Section: Pathophysiology Of Chronic Goutmentioning
confidence: 95%